Abundance and Population Structure of Small Rodents in Fruit and Berry Farms - Linas Balčiauskas; Vitalijus Stirkė; Laima Balčiauskienė (Life, 2023)
Fruit and berry farms are anthropogenic habitats still inhabited by small mammals, though their presence is constantly affected by agricultural activities. Based on trapping data from 2018–2022, we analyzed the abundance and population structure of the dominant rodent species to assess changes in gender and age ratios by year and habitat, the annual and seasonal dynamics of relative abundance, and the relationship between breeding parameters and abundance. The relative abundance of the dominant species, common vole, yellow-necked mouse, striped field mouse, and bank vole, and their proportion in the investigated community varied according to year, season, and habitat. No outbreaks were recorded during the study period. The abundance of the striped field mouse exhibited a downward trend independently of habitat, while the abundance and proportions of the other three species were habitat-dependent. There was no consistent pattern between litter size and relative abundance in the same or following years. Given the ongoing conflict between biodiversity conservation in Europe and agriculture, the results contribute to a better understanding of the functioning and viability of rodent populations in fruit farms and may be used in agroecology and sustainable farming.